2015
DOI: 10.1002/lno.10105
|View full text |Cite
|
Sign up to set email alerts
|

Fish herbivory as key ecological function in a heavily degraded coral reef system

Abstract: Localized impacts, such as eutrophication and overfishing, have been identified as major threats to reefs worldwide, resulting in changes in coral reef community composition, from coral‐dominance to algal‐dominance. Herbivory by fishes is frequently cited as a key process structuring benthic community response to stressors. Here, we experimentally tested the capacity of herbivorous fishes to remove macroalgae along an onshore–offshore spatial gradient in the Spermonde Archipelago, Indonesia; a coral reef syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 57 publications
6
50
0
Order By: Relevance
“…Our results agree with previous studies in the Spermonde Archipelago (Edinger et al, 1998(Edinger et al, , 2000Sawall et al, 2012;Plass-Johnson et al, 2015a, 2016a, where the three sites closer to shore were characterized by low coral cover, higher rubble and higher abundances of turf algae. Cross-shelf variation in these benthic components are related to isotopic metrics of the parrotfish, Chlorurus bleekeri.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results agree with previous studies in the Spermonde Archipelago (Edinger et al, 1998(Edinger et al, , 2000Sawall et al, 2012;Plass-Johnson et al, 2015a, 2016a, where the three sites closer to shore were characterized by low coral cover, higher rubble and higher abundances of turf algae. Cross-shelf variation in these benthic components are related to isotopic metrics of the parrotfish, Chlorurus bleekeri.…”
Section: Discussionsupporting
confidence: 92%
“…Coral reefs closer to shore are generally characterized by less hard coral abundance, an increase in fleshy algae, a general loss of habitat complexity, and by a decrease in coral and fish species diversity or even complete shifts in the sets of species (Fabricius et al, 2005;Plass-Johnson et al, 2015a. Anthropogenic impacts can alter the resource availability and predator-prey relationships on a coral reef thus affecting habitat use and the trophic niche of the biotic constituents (Jones and Syms, 1998;Syms and Jones, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The coral reef system of the Spermonde Archipelago has been the focus of extensive studies in the past two decades, serving as a model system to examine spatial differences in biodiversity, ecological and geological processes, and anthropogenic influences along a cross-shelf gradient within the Coral Triangle (Edinger et al, 1998;Renema and Troelstra, 2001;Cleary et al, 2005;Becking et al, 2006;Sawall et al, 2011Sawall et al, , 2013Hoeksema, 2012;Plass-Johnson et al, 2015a, 2016aPolonia et al, 2015). In this study, we go beyond previous research by identifying several important indicators of water quality and the main environmental drivers of coral reef community composition in the Spermonde Archipelago, including an assessment of temporal trends.…”
Section: Discussionmentioning
confidence: 99%
“…While macroalgae and other invertebrates were relatively low in % cover compared to live coral and turf algae throughout the system, their increased presence and the low live coral cover at <10% in the nearshore sites was linked to poor water quality in this area. Although macroalgae can become abundant where nutrient inputs are high, a recent study (Plass-Johnson et al, 2015a) found nearly no top-down control at the site nearest shore suggesting that water conditions can also be detrimental to macroalgal proliferation. This includes light limitation as well as high DOC, which both have led to negative impacts on corals and marine algae, causing mortality and reduced net photosynthesis (Kline et al, 2006;Meyer et al, 2015).…”
Section: Evidence Of a Cross-shelf Gradient Of Water Quality In Spermmentioning
confidence: 99%
“…Islands found within the archipelago differ in size, are uninhabited to densely populated, and surrounding reefs are exploited to varying degrees and with various techniques. Reef systems are therefore differentially impacted and the health of the reefs differs quite dramatically as a result of these impacts (e.g., bomb fishing, cyanide fishing, sediments, sewage; Plass-Johnson et al, 2015). Located on the southern end of the archipelago's coastline is the city of Makassar with about 1.34 million inhabitants and an industrial harbor.…”
Section: Introductionmentioning
confidence: 99%